Idiosyncratic risks, bailout, and financial crisis: A copula approach - Wang, Daphne; Nguyen, Khoa Huu (Global Business & Finance Review (GBFR), 2015)
EconStor is a publication server for scholarly economic literature, provided as a non-commercial public service by the ZBW.
Publisher: Seoul: People & Global Business Association (P&GBA)

U.S. oil company stock returns and currency fluctuations - Mollick, Andre; Nguyen, Khoa H (Managerial Finance, 2015)
Purpose The purpose of this is paper is to pay a closer look at the 2008-2009 financial crisis (and its aftermath) and analyzes stock returns of nine major US oil companies as well as the oil and gas sector under daily data from January 1992 to April 2012. Design/methodology/approach The authors adopt the arbitrage pricing theory model to examine the relationship between stock returns and their influences including oil price return, yield spreads, and US dollar index return. The authors also provide a test for structural changes in each regression model of return series to capture for multiple breaks. To examine the asymmetric effect of oil price returns on stock returns, the authors separate oil price returns series into two series: positive changes in oil price and negative changes in oil price. Findings The authors find stock returns of oil companies as well as the oil and gas sector are positively affected by oil prices and have stronger effects in the downward direction. Interestingly, The authors find the effects of oil price movements on stock returns increase over time. The authors examine the possibility that investors wishing to hedge against a weakening USD invest in US oil companies and find that more than half of these companies benefit from a weaker USD against the JPY, while all strongly benefit from a weaker USD against major currencies. Originality/value The authors employ daily data for two-decade period including the last global financial crisis. Due to the long-term period covered in this study, sequential Bai-Perron tests are used to detect structural breaks of stock return series. In addition, the data-dependent procedures result in good specifications throughout with white-noise processes in almost all cases.
Keywords: Exchange rates; Oil companies; Oil prices; Stock returns; USA; dept.fin

What explains the change in a firm’s idiosyncratic volatility after a dividend initiation? - Desai, Chintal A.; Nguyen, Khoa H (Managerial Finance, 2015)
Purpose The purpose of this paper is to identify three (maturity, agency, and information) effects that help explain the change in idiosyncratic volatility after a firm initiates a dividend. Design/methodology/approach The paper uses a cross-sectional analysis where the standard errors are adjusted for heteroskedasticity. As for robustness check, the authors perform two-stage analysis to control for potential self-selection bias. The authors also control for 2003 Dividend Tax Cut effect, matching-firm volatility, and confounding events. Findings Using a sample of 688 dividend-initiating firms for a period of 1977 to 2010, the authors find evidence consistent with the hypotheses based on the maturity, agency, and information effects. The volatility changes upon the dividend initiation can be reliably explained by the changes in profit volatility and free cash flow per total assets, and whether the firm consummated a stock split prior to the dividend initiation. The information effect is also found to be economically significant. Originality/value By studying a firm’s decision to initiate a dividend and its impact on the change in its volatility, the research helps contribute to the payout policy and volatility literatures.
Keywords: Dividend initiation; Idiosyncratic volatility; dept.fin

Exceeding expectations: economic forecasts and underreaction to macroeconomic announcements - Birz, Gene; Dutta, Sandip (SSRN Electronic Journal, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00343
Keywords: dept.fin